Jejak Perempuan Buruh Migran dalam Masyarakat ASEAN 2015 - Desintha Dwi Asriani; Ezka Amalia (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
In the embodiment blueprint of ASEAN Community 2015, there are three important elements of the political and security pillar, the pillar of economic, social and cultural pillars. Are assumed to be mutually reinforcing. However, before the ASEAN Community currently limited to realizing economic growth and defense. Women migrant workers issues such precisely NOT SIGN hearts 8 Sector The services will be liberalized. Writing the initials of the Women’s Studies That puts the migrant workers Astra Honda Motor as ISU Main hearts ASEAN Community Discourse 2015. Article Search Google using secondary dataanalysis approach, cCritical notes the issue of women migrant workers and the opportunities that may be managed critically describe.